Biexciton emission from ZnO/Zn0.74Mg0.26O multi-quantum wells - Makino, T. (2009)
Luminescence due to the radiative recombination of localized biexcitons has been observed at low temperature (5 K) in ZnO/Zn0.74Mg0.26O multiquantum wells grown by laser-molecular-beam epilaxy on a lattice-matched ScAlMgO4 substrate (0001). The emission components due to the recombination of localized excitons and biexcitons and due to the exciton–exciton scattering were verified by examining their relative energy positions and intensity dependence on excitation power density. The excitation threshold for biexciton emission was significantly lower than that for exciton–exciton scattering. The binding energy of biexcitons in multi-quantum wells is largely